A Functional Ubiquitin-Proteasome System is Required for Efficient Replication of New World Mayaro and Una Alphaviruses - Yessica Y. Llamas-González; Dalkiria Campos; Juan M. Pascale; Juan Arbiza; José González-Santamaría (Viruses, 2019)
Mayaro (MAYV) and Una (UNAV) are emerging arboviruses belonging to the Alphavirus genus of the Togaviridae family. These viruses can produce febrile disease with symptoms such as fever, headache, myalgia, skin rash and incapacitating poly-arthralgia. Serological studies indicate that both viruses are circulating in different countries in Latin America. Viruses need the host cell machinery and resources to replicate effectively. One strategy to find new antivirals consists of identifying key cellular pathways or factors that are essential for virus replication. In this study, we analyzed the role of the ubiquitin-proteasome system (UPS) in MAYV and UNAV replication. Vero-E6 or HeLa cells were treated with the proteasome inhibitors MG132 or Lactacystin, and viral progeny production was quantified using a plaque assay method. In addition, the synthesis of viral proteins was analyzed by Western blot and confocal microscopy. Our results indicate that treatment with proteasome inhibitors decreases MAYV and UNAV protein synthesis, and also causes a significant dose-dependent decrease in MAYV and UNAV replication. Proteasome activity seems to be important at the early stages of MAYV replication. These findings suggest that the ubiquitin-proteasome system is a possible pharmacological target to inhibit these neglected alphaviruses.